Biomimetic Optimization of Machine Tool Columns Based on Leaf Sequence Structures - Ye, Shuai; Xu, Yun; Wen, Zhuolin; Chen, Ting (International Journal of Mechanical and Electrical Engineering, 2024)
With the goal of enhancing the overall performance of the column, which is one of the key components of the machine tool, a biomimetic design approach was employed in this study. Drawing inspiration from the leaf arrangement structure found in nature, the internal supporting structure of the column was designed using principles and methods of structural biomimicry. Subsequently, finite element static analysis was conducted on the biomimetic column structure. Sensitivity analysis of the optimized pillar structure dimensions was performed, resulting in a comprehensive design solution with superior performance. Following optimization, the mass of the column was reduced by 55.39 kg, representing a decrease of 2.7%; maximum deformation decreased by 0.0738 mm, reducing by 35.18%; maximum equivalent stress decreased by 0.44 MPa, a reduction of 5.4%; and the first-order natural frequency increased by 12.43 Hz, rising by 22.91%. Through effective optimization, while ensuring rigidity, the static and anti-vibration performance of the beam were improved, facilitating lightweight design.